If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-6)+5=2-3(1-x)
We move all terms to the left:
2(x-6)+5-(2-3(1-x))=0
We add all the numbers together, and all the variables
2(x-6)-(2-3(-1x+1))+5=0
We multiply parentheses
2x-(2-3(-1x+1))-12+5=0
We calculate terms in parentheses: -(2-3(-1x+1)), so:We add all the numbers together, and all the variables
2-3(-1x+1)
determiningTheFunctionDomain -3(-1x+1)+2
We multiply parentheses
3x-3+2
We add all the numbers together, and all the variables
3x-1
Back to the equation:
-(3x-1)
2x-(3x-1)-7=0
We get rid of parentheses
2x-3x+1-7=0
We add all the numbers together, and all the variables
-1x-6=0
We move all terms containing x to the left, all other terms to the right
-x=6
x=6/-1
x=-6
| 12a-4=4(3a-1) | | -1=8-b | | 34z+34+36=56 | | 7x+14=3x | | 4m-11=8m+7m | | (X-3)/2-(3X+5)/3=(6x)/5 | | 7(1+2n=-105 | | 8(2+4b)-25b=b | | 14x+2x-15x+5x=18 | | 4(1-x+3x=-2(x+1 | | 5x+1+8x-6=8x+5x-8 | | 3x-11x=-2x+9 | | 2(4x-4)-8=4x2x | | 16v-6v=20 | | 7x-56=2x-12 | | 23/x=207 | | 18j-14j=12 | | -52=4(3w-1) | | 4(j+1.16)=11.32 | | 19-x=2x=3x-5 | | 2.44=4-w | | 11x+18x-8+1=8x+1-8 | | 0.94+2.3d−4.2d=-4.9d−16.46 | | 12x-3=4(3x-4)+1 | | v/2-8=-13 | | 8v+4=36 | | -48=6(w+2) | | 2⋅√x=25−5 | | 4(y-5)-4=-3(-5y+6)-y | | 3x-4=3(x-1)+10 | | 5-x=3x+45 | | 1.2x-1.97=-2.69 |